Use of “Pesticide Impact Rating Index” (PIRI) for evaluating dangers of pesticide use in onion (Allium cepa L.) culture - Aguilar Mora, Paula; Chin Pampillo, Juan; Ruíz Hidalgo, Karla (O Mundo da Saúde, 2014)
Using the program “Pesticide Impact Rating Index” (PIRI) to estimate the risk of the use of 30 insecticides in the culti-vation of onion (Allium cepa L.) for water quality from quebrada Sanatorio, located in the community of Tierra Blanca, in the canton of Carthage, Costa Rica. Information was obtained from the Phytosanitary Service of the State (Servicio Fitosanitario del Estado) and from surveys applied to the producers of the area of Tierra. The results obtained with PIRI were confirmed at the levels of residues of insecticides in sediments and water found in the gorge in a monitoring realized during April, June, August and October, 2011. Approximately 50% of the authorized insecticides qualified as extremely poisonous, and close to 40% qualified as very mobile. On the other hand, from the non registered in-secticides, 60% were catalogued as extremely poisonous, and 40% as very mobile. The water of the gorge is used for irrigation of the cultivation of bordering farms to the river bed, and for that reason this situation can generate problems on public health.